Respuesta :
Answer: It has no solution.
Step-by-step explanation:
Since we have given that
[tex]\frac{3}{m+3}-\frac{m}{3-m}=\frac{m^2+9}{m^-9}[/tex]
We need to find the solution of the above equation:
since is a rational equation so, we will check for its extraneous solution.
[tex]\frac{3}{m+3}-\frac{m}{3-m}=\frac{m^2+9}{m^-29}\\\\\frac{3}{m+3}+\frac{m}{m-3}=\frac{m^2+9}{m^2-9}\\\\\frac{3(m-3)+m(m+3)}{m^2-9}=\frac{m^2+9}{m^2-9}\\\\\frac{3m-9+m^2+3m}{m^2-9}=\frac{m^2+9}{m^2-9}\\\\\frac{m^2-9+6m}{m^2-9}=\frac{m^2+9}{m^2-9}\\\\m^2+6m-9=m^2+9\\\\6m=18\\\\m=\frac{18}{6}=3[/tex]
Hence, the extraneous solution in case of rational equation is 3, when we put m=3, it becomes undefined so, it has no solution.